A bibliometrics analysis of studies on Generation Z's self-perceived careers - Thanh-Hang Pham; Thi Minh-Hang Nguyen; Thi-Cam-Tu La; Xuan-Quynh Hoang; Seng Kiat Kok; Jung Woo Han; Quyen Dang (Cogent Business & Management, 2024)
Recently, Generation Z, born from 1995 to 2010, started entering the labor market and is becoming an important human resource. They will account for 27% of the workforce by 2025, therefore, studying this cohort and how they perceive careers is critically significant. However, literature on Generation Z's self-perceived careers lacks literature summaries that can shed light on the current landscape of the research field. This study employs bibliometric methodologies to identify current research trends, assess state-of-the-art, and indicate future research direction. Results show 108 papers published between 2016 and 2022. Growth trends, geographical locations, leading sources, and authors are identified. Top documents are indicated, with main and trending topics, which provide suggestions for researchers who conduct research in this area.
Keywords: 650; human resource management; Generation Z; career; bibliometric analysis; self-perceived caree